Bacillus and Paenibacillus as plant growth-promoting bacteria in soybean and cannabis - Tariq, Haleema; Subramanian, Sowmyalakshmi; Geitmann, Anja; Smith, Donald L. (Frontiers in Plant Science, 2025)
Many agrochemicals designed to help plants withstand abiotic and biotic stresses can negatively impact the environment. Soil, as an essential natural resource, offers plants organic matter, nutrients, and microbial diversity to thrive in challenging environmental conditions. The soil contains plant growth-promoting bacteria that play an important role in plant/crop productivity, assisting plants through a variety of mechanisms, including nitrogen fixation, phosphate solubilization, phytohormone production, induction of resistance against a wide range of pathogens, and production of microbe-to-plant signals that regulate aspects of plant responses to stress. Plant growth-promoting bacteria such as Bacillus and Paenibacillus can contribute to sustainable agriculture by enhancing nutrient uptake, acting as biocontrol agents, and producing lytic enzymes with the potential to disrupt or destroy pathogenic organisms in important agricultural and medicinal crops including soybean and cannabis. This review explores the mechanisms of action of plant growth-promoting bacteria, focusing on Bacillus and Paenibacillus species, and their potential to enhance, optimize plant growth and promote sustainable agriculture.